Retail Marketing and Sales Performance A Definitive Guide to Optimizing Service Quality and Sales Effectiveness - Preuss, Christoph. (Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
The purpose of this research project is to contribute to effective retail by determining the impacts of the elements of retail marketing interventions on sales performance in franchises and branches. The approach comprises a series of complementary surveys of franchisees, branch managers, shop visitors and customers. This is enriched with secondary data and sector-specific structural detail to determine the direct and mediating effects of retail marketing on sales performance. Through factor analysis results provide evidence that Retail Marketing has a high and positive, direct-structural impact on sales performance. Christoph Preuss contributes to the development of the dichotomy of branch and franchise management by exploring their operational differences. Retailers can exploit retail marketing more effectively if they understand that structural retail marketing parameters make the greatest impact on an outlet’s sales performance.    Contents Retail Marketing, Concepts and Research Model Internal Marketing Sales Performance Human Resources Management     Target Groups Researchers and students of business sciences especially in the field of management Practitioners in marketing, distribution or human resources management      About the author Christoph Preuss holds an MBA from the University of St. Gallen and a doctoral degree from the Bradford University School of Management. He is now a senior sales & marketing executive in the Information and communication Industry.